(untitled) (Chemical Engineering Research Bulletin, 2011)
Polar groups can be introduced on polyethylene by using polar monomer like acryl amide, acrylic acid and methacrylic acid. In present work binary monomer mixture of methacrylic acid and styrene were grafted onto low density polyethylene in the presence of dicumyl peroxide (DCP) as an initiator. Grafted polyethylene was characterized by using differential scanning calorimetry (DSC), melt flow Indexer (MFI) and Fourier transform infrared spectroscope (FTIR). Low value of MFI as compared to virgin polyethylene, presence of carbonyl peaks in the spectrum of grafted polyethylene and higher endothermic peaks in thermogram of grafted polyethylene confirmed grafting of methacrylic acid and styrene onto polyethylene. MFI values at different loads were used for further rheological study of virgin & grafted polyethylene. Key words: Degree of grafting, Meth acrylic acid, Free radical, Vinyl monomer, DCP DOI: http://dx.doi.org/10.3329/cerb.v15i1.7419 Chemical Engineering Research Bulletin 15 (2011) 34-38